2016
DOI: 10.1007/s13202-016-0305-z
|View full text |Cite|
|
Sign up to set email alerts
|

The tectonic uplift since the Late Cretaceous and its impact on the preservation of hydrocarbon in southeastern Sichuan Basin, China

Abstract: Tectonic uplift is the most direct manifestation of tectonic activity, and tectonic deformation strength can be quantitatively shown through uplift height and speed. In this study, balanced rebound and oxygen isotope method are adopted to calculate maximum paleoelevation of stratum uplift of southeastern area of Sichuan Basin since Late Cretaceous due to tectonic activities. And based on current surface elevation of the target area, stratum erosion thickness of southeastern Sichuan during this period is calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Regarding that the generation of a large amount of hydrocarbon predated the Late Yanshanian (Pacific subduction) and Himalayan events (Figure 1c), the structural evolution might have resulted in the modification of the primary hydrocarbon accumulation "pools" and creation of secondary pools as in most overseas and Chinese superimposed cratonic hydrocarbon-bearing sedimentary basins (Dai et al, 2008;Green et al, 1995;Liu et al, 2010;Liu et al, 2017; F I G U R E 8 (a) Seismic section along line BB' (shown on the Figure 2b) showing the main structural styles associated with flexural subsidence: thrust nappe, reverse faults, and detachment zones; pop-up structures; and sets of antithetic and synthetic faults; (b) interpreted seismic section along line AA' (Figure 2b) showing the main petroleum traps, which are essentially of structural types, along with the distribution of hydrocarbon accumulations. The T 1 J 4 + 5 formation flayer acted as a regional cap rock for the lower marine petroleum system and as a barrier rock for the upper continental petroleum system.…”
Section: Hydrocarbon Prospectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding that the generation of a large amount of hydrocarbon predated the Late Yanshanian (Pacific subduction) and Himalayan events (Figure 1c), the structural evolution might have resulted in the modification of the primary hydrocarbon accumulation "pools" and creation of secondary pools as in most overseas and Chinese superimposed cratonic hydrocarbon-bearing sedimentary basins (Dai et al, 2008;Green et al, 1995;Liu et al, 2010;Liu et al, 2017; F I G U R E 8 (a) Seismic section along line BB' (shown on the Figure 2b) showing the main structural styles associated with flexural subsidence: thrust nappe, reverse faults, and detachment zones; pop-up structures; and sets of antithetic and synthetic faults; (b) interpreted seismic section along line AA' (Figure 2b) showing the main petroleum traps, which are essentially of structural types, along with the distribution of hydrocarbon accumulations. The T 1 J 4 + 5 formation flayer acted as a regional cap rock for the lower marine petroleum system and as a barrier rock for the upper continental petroleum system.…”
Section: Hydrocarbon Prospectivitymentioning
confidence: 99%
“…The later tectonic uplift phase related to successive continental collisions, including the Indo-sinian, Yanshanian (Pacific subduction), and Himalayan Orogenies, extended from the Cretaceous to the present (Hao et al, 2008;Korsch, Mai, Sun, & Gorter, 1991;Ma et al, 2008). The associated palaeo-thermal regimes have changed accordingly (Liu, Tang, Chen, & Tang, 2017). These variations in structural evolution and thermal regimes were of great significance on the future of petroleum systems and main events (Yong, Fan, Lv, Tang, & Wang, 2018;Zhu, Qiu, Liu, Xiao, & Hu, 2019).…”
Section: Introductionmentioning
confidence: 99%